Creation: a Catholic's guide to God and the universe - Baglow, Christopher T. (Engaging Catholicism, 2021)
"This book explores the Christian doctrine of creation as both a profound asset to science and the ultimate cause of humility before God. Christian doctrine addresses the why of creation, making it perfectly hospitable to science, which can only help answer the how"--